AgBiome - Baron, James N., (SAGE Knowledge. Cases., 2018)
By 2017, AgBiome employed 80 people and was projecting further expansion. But observers wondered, could a company, which worked on the basis of commitment and without a hierarchy, scale? Co-founders Uknes and Ward believed that the best way to grow was to divide the company into a number of cells. But much work remained to operationalize the cells, including specifying the operational relationship among cells, building a common vocabulary around the development of leadership and culture and even the physical location of the cells. More fundamentally, observers wondered if this division into cells allow the collaboration and openness within the company to continue?